Tissue-specific effects of bacterial PncA overexpression on NAD+ metabolism and aging in mice: implications for tissue-specific aging interventions - Huo, Fengjiao; Zhao, Meili; Liu, Yue; Lv, Shuyao; Feng, Shengyu; Guo, Liuling; Wang, Nan; Zhang, Shuaishuai; Liu, Qing; Mi, Taotao; Wang, Hao; Zhu, Jian-Kang; et al. (Frontiers in Aging, 2025)
BackgroundAs a critical molecule in biological systems, nicotinamide adenine dinucleotide (NAD+) influences the aging of mammals. Therefore, regulation of NAD+ synthesis and degradation may slow aging and mitigate related diseases.ResultsThis study investigated how mammalian tissues rely on different NAD+ synthesis pathways and prefer specific NAD+ precursors. Overexpressing the bacterial nicotinamidase PncA in mice increased NAD+ levels in the liver and kidneys but decreased levels in the heart and hippocampus. In aged mice (25 months old), this overexpression delayed aging indicators by boosting NAD+ levels in the liver and kidneys, indicating potential for PncA to improve age-related decline in these tissues. However, in younger mice (4 months old), PncA overexpression accelerates the senescence of cardiac cells, resulting in a reduction of NAD + levels, increased aging markers, and cognitive decline. These disparate results underscore the necessity of a nuanced, tissue-specific perspective when contemplating the use of NAD+ precursor supplementation as a means of addressing aging.ConclusionOur study highlights the complexity of NAD+ metabolism and its effects on aging in various tissues. It suggests personalized interventions for aging and age-related diseases by showing how different tissues respond to NAD+ precursor manipulation, emphasizing the importance of targeted strategies for optimal therapeutic results with minimal side effects.